2018
DOI: 10.1007/s00421-018-3869-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and psychological determinants of whole-body endurance exercise following short-term sustained operations with partial sleep deprivation

Abstract: PurposeThe study examined the effects of short-term field-based military training with partial sleep deprivation on whole-body endurance performance in well-trained individuals.MethodsBefore and after a 2-day sustained operations (SUSOPS), 14 cadets performed a 15-min constant-load cycling at 65% of peak power output (PPO; CLT65), followed by an exhaustive constant-load trial at 85% of PPO (CLT85). Physiological [oxygen uptake (O2), heart rate (HR), mean arterial pressure (MAP), cardiac output (CO), and region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
3
20
0
1
Order By: Relevance
“…It seems that mental fatigue influences negatively, at least in kayaking, the frequency of the actions. Those results are in line with a previous study 28 showing that a combination of physical and cognitive fatigue affected cadence during a cycling time to exhaustion test.…”
Section: Effect Of Mental Fatigue On Time Trial Performance and Pacingsupporting
confidence: 93%
“…It seems that mental fatigue influences negatively, at least in kayaking, the frequency of the actions. Those results are in line with a previous study 28 showing that a combination of physical and cognitive fatigue affected cadence during a cycling time to exhaustion test.…”
Section: Effect Of Mental Fatigue On Time Trial Performance and Pacingsupporting
confidence: 93%
“…For example, Oliver et al (2009) suggested that a distance test, such as the one used in the current study, might have a smaller signal to noise ratio than incremental exercise tests which were used by Vaara et al (2018) and Goodman et al (1989). These differences are potentially explained by the altered perception of effort experienced following sleep deprivation (Keramidas, Gadefors, Nilsson, & Eiken, 2018), given that incremental tests only require a relatively short period of discomfort in contrast to distance tests. In the current study aerobic performance appears to be impaired due to a consistently lower power output throughout rather than an alteration in pacing strategy (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Across all outcome measures we found considerable individual variation in responses, i.e. not 391 all participants appear to be negatively impacted by sleep deprivation, a trait that is common 392 within similar studies (Keramidas et al, 2018;Oliver et al, 2009). This is an important issue 393 and one that potentially explains some of the conflicting results within the existing literature 394 as it will likely lead to skewed data, which may mask any effects using traditional NHST.…”
mentioning
confidence: 83%
“…The authors attributed these changes in physiological responses to possible alterations in glycogen metabolism and metabolic rate that occur as a result of SD. Keramidas et al [37] reported alterations in aerobic capacity and cardiorespiratory responses during high-intensity constantload cycling following a 51 h trial where participants attained a total of 5 h sleep. Participants performed two constant-load trials, one trial at 65% and another at 85% of their peak power output (PPO).…”
Section: Sleep Loss and Aerobic Performancementioning
confidence: 99%